The ideal L2 selves of Japanese learners of English - Ryan, Stephen (2008)
This thesis attempts to reinterpret language learning motivation through a consideration of the possibilities of applying theories of the self to L2 motivation theory. There were two overriding aims guiding my research; firstly to empirically test theoretical proposals suggesting that the concept of an ideal L2 self may represent a more effective base for understanding L2 motivation, and secondly to explore the possibilities suggested by this approach within the context of the Japanese English learning context.